Method of Identifying the Real State of the Counter Vehicle Based on the Interpretation of Electrical Signals - Olszowiec, Pawel; Luft, Miroslaw (Communications - Scientific letters of the University of Zilina, 2015)
The article presents the analysis of electrical signals and system reports of motor vehicles in which the mileage counter indication has been questioned under service conditions as compared to the vehicles mechanical wear and tear. The essence of the aforementioned deliberations is an attempt at determining the universal procedures allowing for obtaining data concerning the actual vehicle mileage. Search for the intended method results from many factors functioning on the used motor vehicle market. The major factor is the uncontrolled safety level on the roads among the road users and, equally important, financial frauds in the area of motor vehicle sales, as well as vehicle cost estimation by the insurance companies.